Prophetic Communication Strategy in Facing Contemporary Challenges - Basir; Madani, Abu Bakar Idham; Inayah, Siti Syahar; Beta, A Rivai (PT ARRUS Intelektual Indonesia, 2025)
Digital da'wah is not merely a response to technological advancements but also an adaptive prophetic communication strategy in addressing contemporary challenges. This study aims to understand the concept of digital da'wah, the prophetic communication strategies embedded within it, and its relevance in facing the challenges of the modern era. The research employs a literature review methodology. The findings indicate that through information and communication technology, digital da'wah enables the broader, more relevant, and interactive dissemination of Islamic teachings. By emphasizing authenticity, credibility, context, engagement, creativity, and relevance to contemporary settings, digital da'wah can serve as an effective medium for spreading messages of inclusivity, tolerance, and rahmatan lil ‘alamin (a mercy to all creation). The implications of this study highlight digital da'wah as a means for da'wah practitioners to overcome contemporary challenges, expand the reach of da'wah, and contribute positively to strengthening religious understanding and Islamic values in the digital era.